2006
DOI: 10.1176/jnp.18.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Dementia: Dementia With Lewy Bodies and Dementia in Parkinson’s Disease

Abstract: Parkinson's disease with dementia (PD-D) and dementia with Lewy bodies (DLB) may result from the same neurodegenerative process with different temporal and spatial courses. The authors report an association between DLB and family history of dementia in a comparison study between patients with a clinicopathological diagnosis of PD-D and DLB. Findings suggest that positive family history for dementia is associated with DLB with a yet unknown mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…About half of the DLB patients in this study had at least one first degree relative with dementia or PD. This is in line with previous studies, in which a positive family history for dementia was observed in 39-44% and for PD in 10-24% of patients with DLB [10,11]. Nonetheless, the percentages that we found could be an overestimation as patients with insufficient information on family history were not taken into account.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…About half of the DLB patients in this study had at least one first degree relative with dementia or PD. This is in line with previous studies, in which a positive family history for dementia was observed in 39-44% and for PD in 10-24% of patients with DLB [10,11]. Nonetheless, the percentages that we found could be an overestimation as patients with insufficient information on family history were not taken into account.…”
Section: Discussionsupporting
confidence: 91%
“…However, it has been reported that siblings of DLB patients are at higher risk of developing DLB compared to siblings of AD patients [9]. Furthermore, DLB patients more often have a family history of PD or dementia than controls [10,11]. This finding supports the notion that DLB, PD and dementia share, at least partially, the same genetic factors.…”
Section: Introductionsupporting
confidence: 58%
“…Woodruff et al reported a higher percentage of patients with autopsy-confirmed LBD (n = 18) had a family history of dementia (67%) compared to healthy controls (13%) 34 and Papapetropoulos et al reported a family history of dementia was significantly more frequent in DLB subjects (n = 25) compared to PD subjects (n = 64) both with and without dementia and healthy controls. 35 However, Boot et al did not find family history of dementia to be a risk factor for DLB. 5 In line with this research, we found family history of dementia did not predict earlier onset of LBD.…”
Section: Discussionmentioning
confidence: 95%
“…reported a higher percentage of patients with autopsy‐confirmed LBD (n = 18) had a family history of dementia (67%) compared to healthy controls (13%) and Papapetropoulos et al. reported a family history of dementia was significantly more frequent in DLB subjects (n = 25) compared to PD subjects (n = 64) both with and without dementia and healthy controls . However, Boot et al.…”
Section: Discussionmentioning
confidence: 97%
“…location and subtypes of dopaminergic receptors affected) that render patients with dementia less responsive to the pharmacological effects of LD 32, 33, 35–37. In a comparison of PD, PDD, and DLB, Papapetropoulos et al found a lower rate of dyskinesias among DLB patients (16%) compared to PDD (42%) or PD (48%) 38. Others have also reported that dyskinesias occur less often in DLB patients compared to the PDD and PD patients, and this observation may reflect differences in the sensitivity of these patients to dopaminergic medication.…”
Section: Resultsmentioning
confidence: 99%